Analysis of Foreign Policy of the Islamic Republic of Iran by “A Cultural Theory of International Relations”: the Case of Study: Nuclear Diplomacy - Morteza Shokri; seyed Jalal Dehghani Firooz Abadi (رهیافتهای سیاسی و بین المللی)
Most of the theories used in analyzing foreign policy of the Islamic Republic of Iran are based on “Appetite " or "Reason" anthropology. While the logic of Iran's foreign policy in certain issues, such as the nuclear conflict with the West, cannot be analyzed solely on the basis of Appetite and Reason drives such as security and power. In this regard, “A cultural theory of international relations” can provide a framework for analysis of the Ideational aspects of Iran’s foreign policy as it seeks the basis of the international politics in the spirit drive. The question is that, what is the basis of some courageous behaviors of Iran’s foreign policy, in particular it’s nuclear dispute with the West, which has affected the impulses of gaining power and security? By applying of the philosophical anthropology of “A cultural theory of international relations”, we can state this hypothesis that Iran’s foreign policy particularly its nuclear diplomacy is spirit-based. On this basis, the logic and basis for nuclear diplomacy can be analyzed on the basis of two instruments of, aimed at Self-esteem.